Technical efficiency and economies of scale of sugar mills in Mexico - Blas-Cortés, Jonatan; Omaña-Silvestre, José Miguel; Valdivia-Alcala, Ramón; Sandoval-Romero, Fermin; Santiago-Zarate, Ilich Miguel; Valdivia-Cabral, Juanita Japheth (Revista Mexicana de Ciencias Agrícolas, 2023)
During the last decade the sugarcane agroindustry has shown great dynamism by constantly increasing the production of standard sugar and guaranteeing the self-sufficiency of this sweetener in the country, even generating surpluses for export. Nevertheless, even in official documents, it is pointed out that this agroindustry presents a marked technological backwardness and inefficiency. The study was conducted in 2021. This work has two objectives: to estimate the overall technical efficiency by mill and break it down into pure efficiency and scale efficiency, as well as to determine the type of returns to scale of each sugar mill. The method used was the data envelopment analysis and elasticity of scale. The study period was the 2009-2010 harvest, and 54 mills were considered, for which disaggregated information was available. The main finding showed that only 21 mills (38.9%) had an optimal performance as they operated with constant returns to scale. Another 28 mills (51.9%) operated with increasing returns to scale and only five mills (9.3%) operated with decreasing returns to scale. These findings were confirmed by the magnitudes of the elasticity of scale of each group of mills. The main conclusion is that more than ten years ago there was room for mills that operated with increasing returns to scale to be restructured in size and management of inputs over which they have control, which would have allowed improving their overall performance by obtaining economies of scale and improve their pure efficiency and therefore, for the sugarcane agribusiness as a whole.
Keywords: diseconomies of scale; input orientation; returns to scale; sugarcane agroindustry